Despersonalización y desrealización: Una aproximación filosófica desde el análisis de casos (2010)
The objective of this paper is to demonstrate that a substantial difference exists between the derealization and depersonalization disorders. The fundamental arguments point out that each one of these disorders has a specific symptomatic presentation, that the descriptions made by patients about their experiences have different contents and forms, and that a particular theoretical proposal can be elaborated to explain the manner in which each one of these disorders it is articulated. In order to achieve that objective, a logical and conceptual analysis of a clinical erealización and depersonalization case is developed. A dyadic theory about each one of these disorders is offered. For the derealization a model whereby the relationships between the World and the Self are the core of the discussion is proposed. And for depersonalization, a model whereby the Body and the Self have the priority is presented. The paper arrives at the conclusion that derealization and depersonalization can be considered and conceptualized as different entities, although they can be presented in relational or causal way.